The Function of the Middle Building in Late Bronze Age Jericho - Gardner, Anne E. (Buried History: The Journal of the Australian Institute of Archaeology, 2010)
The Middle Building is one of the few structures dated to the Late Bronze Age at Jericho. It has been recognized as a residence but also hypothesized to have been a fort. On the basis of its location and some features it shares with the Stratum IXb structure at Tell Halif, it is argued that the Middle Building in Jericho was more than a private dwelling. Rather, it is likely to have been a way station that was part of the Egyptian administration.